Characterization of a Novel Thermostable (S)-Amine-Transaminase from an Antarctic Moderately-Thermophilic Bacterium Albidovulum Sp. slm16 - Blamey-Alegria, J (Elsevier Inc., 2019)
Amine-transaminases (ATAs) are enzymes that catalyze the reversible transfer of an amino group between primary amines and carbonyl compounds. They have been widely studied in the last decades for their application in stereoselective synthesis of chiral amines, which are one of the most valuable building blocks in pharmaceuticals manufacturing. Their excellent enantioselectivity, use of low-cost substrates and no need for external cofactors has turned these enzymes into a promising alternative to the chemical synthesis of chiral amines. Nevertheless, its application at industrial scale remains limited mainly because most of the available ATAs are scarcely tolerant to harsh reaction conditions such as high temperatures and presence of organic solvents. In this work, a novel (S)-ATA was discovered in a thermophilic bacterium, Albidovulum sp. SLM16, isolated from a geothermal Antarctic environmental sample, more specifically from a shoreline fumarole in Deception Island. The transaminase-coding gene was identified in the genome of the microorganism, cloned and overexpressed in Escherichia coli for biochemical characterization. The activity of the recombinant ATA was optimal at 65 °C and pH 9.5. Molecular mass estimates suggest a 75 kDa homodimeric structure. The enzyme turned out to be highly thermostable, maintaining 80% of its specific activity after 5 days of incubation at 50 °C. These results indicate that ATA_SLM16 is an excellent candidate for potential applications in biocatalytic synthesis. To the best of our knowledge, this would be the first report of the characterization of a thermostable (S)-ATA discovered by means of in vivo screening of thermophilic microorganisms. © 2019